Generation z’s evaluation of jamu as a herbal drink: implications for consumer purchase decisions - Rano Abryanto; Shafira Nindhita (Journal of Gastro Tourism, 2026)
Jamu as traditional herbal beverages are a big part of Indonesia's cuisine and health culture. But we still don't completely understand how important they are in current hospitality consumption, especially among those in Generation Z. This research investigates impact of the influence of perceived value of Jamu on the purchase choices of Generation Z consumers in hospitality and healthy-live daily settings. This study examines perceived value as a cognitive evaluation formed through awareness and perception, while family context is treated as a social influence that shapes how this value is constructed. On the other hand, decisions on what to buy are based on how customers act and why they want to buy. We collected information from 125 users who had already utilized Jamu. A quantitative technique was employed, utilizing descriptive statistics and simple linear regression, to analyse the association between perceived value and purchase outcomes. The findings indicate that Generation Z's purchasing decisions are considerably influenced by their perception of Jamu's value. Perception is the most essential value factor, followed by awareness and family context. The findings show that even though Jamu is based on tradition, Generation Z is more likely to self-minded it if they think it is safe, useful, and relate to their healthy-lives today. These findings highlight the imperative for hotel operators and foodservice providers to recontextualize traditional herbal beverages through immersive presentation, contemporary branding, and targeted marketing strategies.